THE EFFECT OF TAX KNOWLEDGE, TAX SANCTIONS, E-FILING ON TAX COMPLIANCE - Wibowo, Jeanne Yemima; Yanti, Yanti (Graduate Program of Universitas Tarumanagara, 2024)
The purpose of this study was to determine the level of tax compliance as influenced by tax knowledge, tax sanctions, and e-filing. The population used in this study were relatives and office colleagues of researchers. The sample taken was 115 respondents. The sample selection used convenience sampling and simple random sampling methods. In this study, researchers processed data using SmartPLS software version 3.0. Based on the results of the research conducted, tax sanctions have no effect on tax compliance. On the other hand, tax knowledge and e-filing have an influence on tax compliance. This is certainly in line with compliance theory which explains a person's compliance with the orders or rules applied.